Clinical and molecular characteristics of a Brazilian family with spinocerebellar ataxia type 1 Características clínicas e moleculares de uma família Brasileira com ataxia espinocerebelar tipo 1 - Iscia Lopes-Cendes; Carlos E. Steiner; Isabel Silveira; Walter Pinto-Junior; Jayme A. Maciel; Guy A. Rouleau (Arquivos de Neuro-Psiquiatria)
The spinocerebellar ataxias (SCAs) are a clinically and genetically heterogeneous group of late onset neurodegenerative disorders. To date, seven different genes causing autosomal dominant SCA have been mapped: SCA1, SCA2, Machado-Joseph disease (MJD)/SCA3, SCA4, SCA5, SCA7 and dentatorubropallidoluysian atrophy (DRPLA). Expansions of an unstable trinucleotide CAG repeat cause three of these disorders: SCA1, MJD/SCA3 and DRPLA. We studied one Brazilian family segregating an autosomal dominant type of SCA. A total of ten individuals were examined and tested for the presence of the SCA1, MJD and DRPLA mutations. Three individuals, one male and two females, were considered affected based on neurological examination; ages at onset were: 32, 36 and 41 years. The first complaint in all three patients was gait ataxia which progressed slowly over the years. Six individuals showed one allele containing an expanded CAG repeat in the SCA1 gene. The mean size of the expanded allele was 48.2 CAG units. Instability of the expanded CAG tract was seen in the two transmissions that were observed in this family. In both occasions there was a contraction of the CAG tract. Our study demonstrates that SCA1 occurs in the Brazilian population. In addition, our results stress the importance of molecular studies in the confirmation of diagnosis and for pre-symptomatic testing in SCAs. As ataxias espinocerebelares (AECs) fazem parte de um grupo de doenças neurodegenerativas que apresentam grande heterogeneidade clínica e genética. Existem até o momento sete genes mapeados responsáveis pelas AECs de transmissão autossômica dominante: SCA1, SCA2, doença de Machado-Joseph (DA/7) ou SCA3, SCA4, SCA5, SCA7 e atrofia dentatorubropalidoluisiana (ADRPL). Uma expansão de um trínucletídeo CAG foi identificada como a mutação responsável na SCA], DMJ e ADRPL. Estudamos uma família brasileira com uma forma autossômica dominante de AEC. Dez indivíduos foram examinados e amostras de sangue foram colhidas para os estudos moleculares das mutações causadoras da SCA1, DMJ e ADRPL. Três membros da família foram considerados clinicamente afetados, um indivíduo do sexo masculino e dois do sexo feminino. A idade de início dos sintomas foi 32, 36 e 41 anos. Ataxia da marcha, lentamente progressiva, foi a primeira manifestação da doença nos três pacientes. Em seis indivíduos os estudos moleculares mostraram um alelo com expansão da sequência CAG contida no gene SCA1. O tamanho médio do alelo CAG expandido foi 48,2 unidades. O alelo SCA 1 expandido apresentou instabilidade nas duas trasmissões observadas, nas quais ocorreram contrações de uma e de seis unidades CAG. O nosso estudo mostra que a SCA1 ocorre na população brasileira. Além disso, os nossos resultados reforçam a importância dos estudos moleculares na confirmação diagnostica e no diagnóstico pré-sintomático de pacientes com AEC.